A single episode of high intensity sound inhibits long-term potentiation in the hippocampus of rats. Issue 1 (December 2017) - Deus, J.; Cunha, A.; Terzian, A.; Resstel, L.; Elias, L.; Antunes-Rodrigues, J.; Almeida, S.; Leão, R.
Abstract Exposure to loud sounds has become increasingly common. The most common consequences of loud sound exposure are deafness and tinnitus, but emotional and cognitive problems are also associated with loud sound exposure. Loud sounds can activate the hipothalamic-pituitary-adrenal axis resulting in the secretion of corticosterone, which affects hippocampal synaptic plasticity. Previously we have shown that long-term exposure to short episodes of high intensity sound inhibited hippocampal long-term potentiation (LTP) without affecting spatial learning and memory. Here we aimed to study the impact of short term loud sound exposure on hippocampal synaptic plasticity and function. We found that a single minute of 110 dB sound inhibits hippocampal Schaffer-CA1 LTP for 24 hours. This effect did not occur with an 80-dB sound exposure, was not correlated with corticosterone secretion and was also observed in the perforant-dentate gyrus synapse. We found that despite the deficit in the LTP these animals presented normal spatial learning and memory and fear conditioning. We conclude that a single episode of high-intensity sound impairs hippocampal LTP, without impairing memory and learning. Our results show that the hippocampus is very responsive to loud sounds which can have a potential, but not yet identified, impact on its function.